OGA activated glycopeptide-based nano-activator to activate PKM2 tetramerization for switching catabolic pathways and sensitizing chemotherapy resistance. (May 2022) - Hou, Da-Yong; Xiao, Wu-Yi; Wang, Jia-Qi; Yaseen, Muhammad; Wang, Zhi-Jia; Fei, Yue; Wang, Man-Di; Wang, Lu; Wang, Hui; Shi, Xinghua; Cai, Meng-meng; Feng, Hai-Tao; et al.
Abstract: Tumor cells intensively engage in metabolic reprogramming for enhancing the availability of glycolytic metabolites and support cell proliferation. As the most important rate-limiting enzyme in aerobic glycolysis, activating the pyruvate kinase muscle isoform 2 (PKM2) from dimers to tetramers has become a key tumor chemotherapy method to control glucose metabolism. Herein, we developed a glycopeptide-based PKM2 nano-activator, which could induce the tetramerization of PKM2 based on serine bonding to Domain C of PKM2. The bound and trapped PKM2 tetramers significantly hindered glycolytic intermediates, prevented the nucleus translocation of dimeric PKM2, and ultimately inhibited the proliferation, chemoresistance and metastasis of tumor. The glycopeptide assembled into nanoparticles under aqueous conditions and in the circulation, which in situ transformed into PKM2 nano-activator with nanofibrillar structure after specifically activated by O-GlcNAcase recognition upregulated in a wide range of human tumors. Moreover, the glycopeptide-based PKM2 nano-activator successfully accumulated at the tumor sites and boosted the chemo-drug sensitivity against prostate and breast cancers. Attributed to these intriguing results, the newly developed glycopeptide-based PKM2 nano-activator can be envisioned a promising candidate for the treatment of tumors by switching catabolic pathways. Graphical abstract: Schematic illustration of self-assembly, accumulation and in situ fibrillar transformation of GPNA1 in tumor cells, followed by intracellular anti-proliferative events. Image 1